Climate change: Minimizing the risks and maximizing the benefits for the poor - International Food Policy Research Institute (International Food Policy Research Institute, 2008)
Global climate change poses great risks to poor people whose livelihoods depend directly on agriculture, forestry, and other natural resource uses. IFPRI's climate change research focuses on the assessment of, adaptation to, and mitigation of these risks. Strategic, cost-effective, and pro-poor policy reforms that enhance human welfare in equitable and sustainable ways form the core ofIFPRI's Global Change Program. The Program analyzes the complex interrelations between climate change and agricultural growth, food security, and natural resource sustainability. The Program's comprehensive approach to climate change analysis looks at the key drivers of climate change and their possible evolution over time. A scenariobased framework is used to forecast how these major drivers of change will impact food and agricultural systems and food security. Based in part on these projections, IFPRI is developing adaptation and mitigation strategies, including ones that show how alternative climate policy regimes in a post-Kyoto-Protocol world will affect agriculture, food security, and poor people. Developing countries could finance climate adaptation and mitigation strategies through cap-and-trade and carbon-tax instruments that support agricultural and rural development, but the impacts of these and other approaches need to be better understood. Effective adaptation and mitigation can generate income in rural areas, further increasing local capacity to adapt to climate change, but the best means of encouraging these outcomes need to be identified.